Pros and cons of continous glucose monitoring (Journal of Medical Science, 2023)
Introduction. Diabetes mellitus is a metabolic disorder that might result in short and long-term health complications and even death if not properly managed. This disease affected 451 million people in 2017 worldwide and these figures are expected to increase to 693 million by 2045. Currently, there is no cure for diabetes. However, self-management, especially keeping BG in the recommended range, is crucial to the treatment. Aim. The aim of this paper is to offer an overview of current literature regarding CGM technologies. We outline mechanism of action, current use of CGM and discuss pros and cons of using this method in DM management. Material and methods. A review of the literature available in PubMed and Google Scholar databases was conducted. Results and conclusions. Blood glucose measurement using a glucometer is an invasive method, not very comfortable for the patient, it detects only one temporary blood glucose level. This method does not reflect glucose fluctuations and trends, which makes effective diabetes management difficult. Even supplementing this method with HbA1c measurement does not bring as much relevant information for making therapeutic decision as CGM. The abundance of data provided by CGM and the ability to analyze them in greater detail, provide additional information to help achieve glycemic goals. It is a discreet and minimally invasive method, and the reading of blood glucose values can be easily read from mobile device. Data storage allows the doctor to view the past course of the disease and modify treatment. Manufacturers are constantly improving their devices, eliminating flaws, and the benefits of CGM improve treatment outcomes, which should translate into a reduction in the long-term complications of diabetes. Further research is needed, leading to the development of CGM technology.